2006
DOI: 10.1104/pp.106.089458
|View full text |Cite
|
Sign up to set email alerts
|

Plant Glutathione Peroxidases Are Functional Peroxiredoxins Distributed in Several Subcellular Compartments and Regulated during Biotic and Abiotic Stresses

Abstract: We provide here an exhaustive overview of the glutathione (GSH) peroxidase (Gpx) family of poplar (Populus trichocarpa). Although these proteins were initially defined as GSH dependent, in fact they use only reduced thioredoxin (Trx) for their regeneration and do not react with GSH or glutaredoxin, constituting a fifth class of peroxiredoxins. The two chloroplastic Gpxs display a marked selectivity toward their electron donors, being exclusively specific for Trxs of the y type for their reduction. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
339
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 355 publications
(363 citation statements)
references
References 64 publications
19
339
1
4
Order By: Relevance
“…Whereas the spectra of poplar TxP reflect a switch from a hydrophobic environment in the reduced state to an exposed conformation in the oxidized state (43), the tryptophan fluorescence emission spectra of oxidized and reduced Px III are identical and in accordance with an exposed position of Trp 137 in both forms (supplemental Fig. S4).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas the spectra of poplar TxP reflect a switch from a hydrophobic environment in the reduced state to an exposed conformation in the oxidized state (43), the tryptophan fluorescence emission spectra of oxidized and reduced Px III are identical and in accordance with an exposed position of Trp 137 in both forms (supplemental Fig. S4).…”
Section: Discussionmentioning
confidence: 93%
“…This loop is not present in the monomeric human GPX4 (PDB code 2GS3 and 2OBI (42)) as well as in most of the cysteine-containing glutathione peroxidase-type proteins including poplar TxP (16). Nevertheless, the latter forms a homodimer (42,43). This protein dimerizes through the C-terminal region (16).…”
Section: Resultsmentioning
confidence: 99%
“…This function was clearly demonstrated by genetic means for some chloroplast thioredoxins (Vieira Dos Santos and Rey, 2006). An antioxidant function of the NTS is suggested even in the cytosol and mitochondria by the presence of the misnamed plant glutathione peroxidases (GPXs), which are in fact thioredoxin-dependent peroxidases (Iqbal et al, 2006;Navrot et al, 2006), and of peroxiredoxins (PRXs), some reducible by thioredoxins (Brehelin et al, 2003) and others by glutaredoxins (Dietz, 2003). The simplest interpretation is that the alternative thioredoxin reduction pathway is sufficient to allow optimal function of the GPXs and PRXs in the ntra ntrb mutant.…”
Section: The Ntra Ntrb Mutant Is Not Hypersensitive To Oxidantsmentioning
confidence: 99%
“…Including glutathione peroxidases, there are five classes of thioredoxin peroxidases in plants based on their amino acid sequence and oligomerization state . Several of them are solely dependent on thioredoxin for their regeneration (Rouhier et al 2004b;Navrot et al 2006), but surprisingly our initial data which concerned a specific class called atypical type II peroxiredoxin (later referred to as poplar PrxIIB) indicated that they could be regenerated equally well by thioredoxin and glutaredoxin (Rouhier et al 2001(Rouhier et al , 2002a. That glutaredoxins could be an alternate reducing system to atypical type II peroxiredoxins was unknown at that time in other biological organisms.…”
Section: Redox Regulation Backgroundmentioning
confidence: 99%